2019
DOI: 10.1016/j.clnu.2018.07.023
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of nutritional interventions in older adults at risk of malnutrition across different health care settings: Pooled analyses of individual participant data from nine randomized controlled trials

Abstract: Based on pooled data of older adults (at risk of malnutrition), nutritional interventions have a positive effect on energy intake and body weight. Dietary counseling combined with ONS is the most effective intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(49 citation statements)
references
References 38 publications
1
48
0
Order By: Relevance
“…The purpose was to provide simple instruction on modifying food intake (e.g., food fortification, meal plan adaptation) to improve nutritional intake, which could be replicated in primary care, outside of a clinical trial setting. This is not the same as intensive, individualised dietary counselling by a dietitian, which combined with ONS may be the optimal strategy [43]. This approach can however be restricted by limited resources of the dietetic profession, especially in the primary care setting, as such DA was chosen for this study as it represents a pragmatic and viable nutritional first line intervention in this setting.…”
Section: Discussionmentioning
confidence: 99%
“…The purpose was to provide simple instruction on modifying food intake (e.g., food fortification, meal plan adaptation) to improve nutritional intake, which could be replicated in primary care, outside of a clinical trial setting. This is not the same as intensive, individualised dietary counselling by a dietitian, which combined with ONS may be the optimal strategy [43]. This approach can however be restricted by limited resources of the dietetic profession, especially in the primary care setting, as such DA was chosen for this study as it represents a pragmatic and viable nutritional first line intervention in this setting.…”
Section: Discussionmentioning
confidence: 99%
“…After stratifying by the type of intervention, the intervention effect was significant only for an increase in energy intake when dietary counseling was given in combination with ONS (OR 2.28; CI 1.90, 2.73). Therefore, for older adults at risk of PEM, they identified nutritional interventions had a positive effect on energy intake and body weight, and dietary counseling combined with ONS was the most effective intervention [48].…”
Section: Pemmentioning
confidence: 99%
“…This support significantly lowered the risk of experiencing adverse clinical outcomes after 30 days, reduced all-cause mortality, and improved the patients’ functional status and quality of life [ 18 ]. Another systematic review found that nutritional interventions, such as prescribing oral nutritional supplements (ONS), were most effective if they were combined with dietary counselling by a dietitian [ 19 ]. Another study showed that tube-fed patients received 10% more energy and about 8% more protein from enteral formula prescribed by dietitians than formula prescribed by physicians.…”
Section: Introductionmentioning
confidence: 99%